Uncovering corporate tax avoidance and investigating multinational corporation financial strategies and the social consequences - Ciganskis, Domeniks (Riga Graduate School of Law, 2023)
This bachelor thesis’s aim is to analyze and research the problem of corporate tax avoidance and its social consequences. The main objectives will be to first of all, address and explain the theory of corporate tax in general, which includes the strategies, tax theory, and an in-depth example of one of these strategies – tax havens. Furthermore, this bachelor’s thesis will analyze case law with specific case examples of three companies – Nike, Engie, and Amazon in relation to the in-depth example of the tax haven tax avoidance strategy. Further on, the bachelor thesis will analyze what are the social consequences, economic consequences as well as the ethical measures of tax avoidance, combined together with a legal perspective. This bachelor paper concludes that while there are a lot of legal measures taken into anti-tax avoidance procedures, these frameworks are often inadequate or ineffective.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Tax law; corporate tax avoidance; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law